2007
DOI: 10.1242/jcs.03490
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide P2Y1 receptor regulates EGF receptor mitogenic signaling and expression in epithelial cells

Abstract: Epidermal growth factor receptor (EGFR) function is transregulated by a variety of stimuli, including agonists of certain G-protein-coupled receptors (GPCRs). One of the most ubiquitous GPCRs is the P2Y1 receptor (P2RY1, hereafter referred to as P2Y1R) for extracellular nucleotides, mainly ADP. Here, we show in tumoral HeLa cells and normal FRT epithelial cells that P2Y1R broadcasts mitogenic signals by transactivating the EGFR. The pathway involves PKC, Src and cell surface metalloproteases. Stimulation of P2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
51
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 85 publications
7
51
0
Order By: Relevance
“…It remains questionable whether the consensus motif-like C-terminal domain KPPTEPTPSP (aa 321-330) of the mouse P2Y 2 receptor is functional. P2Y 1 -induced transactivation of the EGF receptor was recently reported for tumoral HeLa cells and FRT epithelial cells (Buvinic et al, 2007). At present, the mechanism leading to the potential transactivation of the EGF receptor by ADPβS has not been defined.…”
Section: Differences Between P2 Receptor Agonists and Targetsmentioning
confidence: 94%
“…It remains questionable whether the consensus motif-like C-terminal domain KPPTEPTPSP (aa 321-330) of the mouse P2Y 2 receptor is functional. P2Y 1 -induced transactivation of the EGF receptor was recently reported for tumoral HeLa cells and FRT epithelial cells (Buvinic et al, 2007). At present, the mechanism leading to the potential transactivation of the EGF receptor by ADPβS has not been defined.…”
Section: Differences Between P2 Receptor Agonists and Targetsmentioning
confidence: 94%
“…The key signaling components required for EGFR transactivation following ␤1AR stimulation include: 1) C-terminal phosphorylation of activated ␤1ARs by GRK5/6, and 2) recruitment of both ␤-arrestins 1 and 2 to phosphorylated ␤1ARs. Recruitment of ␤-arrestins to activated ␤1ARs allow subsequent activation of c-Src and matrix metalloproteinases, cleavage of HB-EGF and activation of EGFR, processes that contribute to transactivation pathways defined for other 7TMRs (2)(3)(4)(5)(6)(7). Trafficking of EGFR has been shown to be critical in defining downstream signaling pathways regulated by ligand-induced activation (8).…”
Section: ␤1-adrenergic Receptor (␤1ar)mentioning
confidence: 99%
“…Strikingly, the canine kidney epithelial cell line which ectopically expresses P2Y 1 receptors displays a highly proliferative phenotype that depends on EGFR activity associated with an increased level of EGFR. This discloses a novel aspect of GPCRmediated regulation of EGFR function [77]. Similarly, an in vitro wound healing assay performed in human corneal and BEAS 2B (human bronchial) epithelial cells suggested that ATP released as a consequence of the wound triggers EGFR transactivation resulting in the stimulation of the PI3K and ERK signalling pathways to lead wound closure [78].…”
Section: P2 Receptors and Rtksmentioning
confidence: 74%
“…This could be explained by the fact that the EGFR function is transregulated by a variety of stimuli, including agonists of certain GPCRs [77]. Different P2Y receptor subtypes have been involved in the transactivation of the EGFR in normal and cancer cells.…”
Section: P2 Receptors and Rtksmentioning
confidence: 99%